Acute Limb Ischemia After Cardiac Surgery: Looking for the White Clot Syndrome - Rémy Hamdan; Valentin Crespy; Georges Tarris; Philippe Savard (Annals of Internal Medicine: Clinical Cases)
Two weeks after undergoing cardiac surgery with cardiopulmonary bypass, a 59-year-old patient presented with acute right-limb ischemia. The probability of heparin-induced thrombocytopenia was high and heparin antibody immunoassays were positive, so heparin anticoagulation was replaced by argatroban. An emergency right femoral thrombectomy yielded a macroscopically white thrombus that was rich in platelets and leukocytes on histopathological and immunologic analysis. Given that the serotonin-release assay is the gold standard and is technically demanding, type 2 heparin-induced thrombopenia is challenging to diagnose with certainty after cardiac surgery, so the white appearance of a thrombus obtained by emergency thrombectomy may help in decision-making.